Benthic polychaetes as bioindicators of organic matter in the intertidal zone of Santa Clara Island (Gulf of Guayaquil Exterior) (Revista Científica Ciencias Naturales y Ambientales, 2013)
This study was developed during the months of September and November 2007, at the Santa Clara Island area. Eight sampling stations were established in the intertidal zone of the island. At each sampling benthic organisms, samples of sediment, organic matter (MO) were collected and environmental variables: temperature, salinity and pH in seawater were registered. The rates of diversity and equity were applied. The goal of this paper is to study the community of polychaetes in the intertidal zone of the Santa Clara Island using them as organic matter bioindicators. In September, the highest diversity index (1.47 bits / ind) was located at station 4 with the lowest concentration of MO (1.9%) and the lowest diversity index (0,21bits/ind) at station 7 with the highest concentration of MO (9.9%). While in the month of November the highest diversity index (2.01 bits / ind) station was located at Station 1, a place of lower concentration of MO (3.8%) and the lowest diversity index (1.14 bits / ind) at station 6 site with a lower concentration of MO (1.2%) and station 7 site with the highest concentration of MO (9.9%) and relatively greater diversity value (1.69 bits / ind). In September where is applicable equity index, season 4 (0.70) presents a more uniform distribution and a less homogeneous station was No. 7 (0.19). In November the station which presented the most homogeneous distribution was station 7, with a value of 0.87 respectively. The station that presented the least homogeneous distribution was station 4 with a value of 0.52.
Keywords: Polychaeta; organic matter (MO); diversity; equity